Refurbishment of public housing villas in the United Arab Emirates (UAE): energy and economic impact - Abu-Hijleh, Bassam (2016)
This study aims at assessing the technical and economic benefits of refurbishing existing public housing villas in the UAE. Four representative federal public housing villas built between 1980s and 2010s were modeled and analyzed. The Integrated Environmental Solutions-Virtual Environment (IES-VE) energy modeling software was used to estimate the energy consumption and savings due to different refurbishment configurations applied to the villas. The refurbishment technical configurations were based on the UAE’s Estidama green buildings sustainability assessment system. The refurbishment configurations include upgrading three elements: the wall and roof insulation as well as replacing the glazing. The annual electricity savings results indicated that the most cost-efficient refurbishment strategy is upgrading of wall insulation (savings up to 20.8 %) followed by upgrading the roof’s insulation (savings up to 11.6 %) and lastly replacing the glazing (savings up to 3.2 %). When all three elements were refurbished simultaneously, savings up to 36.7 % were achieved (villa model 670). The savings translated to CO2 emission reduction of 22.6 t/year. The simple and discounted payback periods for the different configurations tested ranged between 8 and 28 and 10 and 50 years, respectively.